Central African Economic and Monetary Community : Staff Report on Common Policies of Member Countries;. (IMF Staff Country Reports; Country Report ;, 2006)
Macroeconomic developments benefited from oil windfalls, but structural problems still impede non-oil growth. Fiscal and external balances improved in the Central African Economic and Monetary Community (CEMAC) because of the surge in oil prices and better fiscal management. Oil-related reserve inflows also helped accelerate regional broad money, leading to somewhat higher inflation and a small further appreciation of the real effective exchange rate (REER). Macroeconomic prospects for 2006 are positive, despite persistent structural challenges. Higher oil income offers CEMAC members economic opportunities but also challenges.